Implementation Of English Language Learning For Elementary School Students - Ibnumal, Ibnumal; Yulianti, Andi; Mardiana, Mardiana (Ridwan Institute, 2026)
The global significance of English underscores the need for effective early language instruction. This study aims to evaluate the implementation of English language learning in elementary schools and its correlation with student learning outcomes. A quantitative approach with a correlational design was employed. The research subjects were 30 fifth-grade students selected through simple random sampling from an elementary school in Pangkajene. Data were collected using a learning implementation questionnaire and an English learning outcome test. The questionnaire’s validity and reliability were tested prior to use. Data were analyzed using descriptive statistics and Pearson’s correlation test. The results indicated that the implementation of English language learning was in the “good” category (average percentage 85.2%), with the highest aspect being teacher–student interaction (90%). Student learning outcomes were also in the “good” category (average score 78). A significant positive correlation (r = 0.68; p < 0.05) was found between the implementation of learning and student outcomes, accounting for 46.2% of the variance. This finding confirms that the quality of learning implementation plays a crucial role in enhancing students’ English skills. The study implies the need for continuous improvement in learning methods and media to further optimize student achievement.